Prevalence and Associated Factors of Weight Management among 18-79 Years Old in Beijing - Yingqi WEI, Aijuan MA, Kai FANG, Jing DONG, Jin XIE, Chen XIE, Zhong DONG (Zhongguo quanke yixue, 2022)
Background Weight management should be extended to the entire population and not limited to special populations. Exploring the willingness, status, measures and influencing factors of adults' weight management, may contribute to the development of a reasonable, scientific, and easily operable method for reaching or maintaining a healthy weight. Objective To understand the prevalence and associated factors regarding achieving or maintaining a healthy weight in residents aged 18-79 in Beijing. Methods A survey was conducted from August to December 2017 with a stratified multistage sample of 13 188 permanent residents aged 18-79 from Beijing's 16 districts using a self-compiled questionnaire for understanding their self-assessed weight, weight changes within the past 12 months, and use of methods for weight control. The prevalence of weight management was compared by different characteristics. Methods for weight management used by weight controllers were comparatively analyzed by sex and age. We explored the differences in daily dietary habits and physical activity between weight controllers and non-weight controllers. Multivariate Logistic regression was used to analyze the factors associated with the implementation of weight management. Results The overall prevalence of weight management in the residents over the last 12 months was 29.90% (3 947/13 188) . The prevalence of weight management differed statistically by sex, marital status, level of education, diabetes prevalence, current smoking status, physical activity status, voluntary health check-ups, assessment of weight, change in weight over the past 12 months, and BMI (P<0.05) . Diet control〔87.31% (3 446/3 947) 〕 and physical exercise〔78.34% (3 092/3 947) 〕were the most widely used weight management methods. The proportion of men who used physical exercise and smoking for weight control was significantly higher than that of women (P<0.001) , whereas the proportion of women who used diet control and weight loss medications for weight control was significantly higher than that of men (P<0.05) . The proportion of residents who used physical exercise and smoking for weight control was differed statistically by age groups (P<0.05) . 2 668 cases (67.60%) used both diet control and physical exercise to control weight, among whom 60-70 year olds accounted for a higher percentage than did 18-44 year olds and 45-59 year olds (P<0.001) . 625 cases (15.83%) relied only on diet control to control weight, among whom 18-44 year olds accounted for a higher percentage than did 45-59 year olds and 60-79 year olds (P<0.001) . The prevalence of weight management by physical activity or smoking differed significantly across age groups. Compared with non-weight controllers, weight controllers had lower prevalence of inadequate intake of fresh fruit and vegetables and excessive intake of red meat (P<0.05) . Moreover, they had higher prevalence of doing ≥ 150 min of moderate to vigorous intensity activities per week (P<0.001) . Furthermore, they had higher prevalence of spending ≥4 hours per day in leisure-time sedentary behaviors (P<0.001) . Multivariate regression analysis showed that age<60 years, women, married/unmarried cohabitation, higher level of education (junior high school and above) , current non-smoking, alcohol consumption within the past 7 days, physical inactivity, voluntary physical examinations, correctly assessing one's own weight, weight gain/loss ≥ 2.5 kg in the past 12 months, and having a BMI within the range of normal to obesity were associated with higher possibility of implementing weight management (P<0.05) . Conclusion In these Beijing residents aged 18-79 years, diet control and increased exercise were popular for weight control, but the use of unhealthy weight management methods was also found. When guiding residents to use proper methods to control weight, individualized management programs should be developed with sex, age, education level and other factors taken into consideration.